2012
DOI: 10.1016/j.plefa.2012.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of marine-derived n-3 fatty acids in Icelanders, Japanese, Koreans, and Americans—A descriptive epidemiologic study

Abstract: SummaryIn the 1990's Iceland and Japan were known as countries with high fish consumption whereas coronary heart disease (CHD) mortality in Iceland was high and that in Japan was low among developed countries. We described recent data fish consumption and CHD mortality from publicly available data. We also measured CHD risk factors and serum levels of marine-derived n-3 and other fatty acids from population-based samples of 1,324 men in Iceland, Japan, South Korea, and the US. CHD mortality in men in Iceland w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…Of interest, supplementation of the diet with omega-3 fatty acids attenuates the production of proinflammatory cytokines (37) and increases the amounts of SPMs in peripheral blood (15, 38). A study identified that omega-3 essential fatty acids, the precursors of SPMs, were biomarkers of a lower risk for fatal coronary heart disease (39, 40). Hence, our results suggest a potential physiologic mechanism by which coagulation initiates the endogenous production of functional n-3-derived SPMs that affect innate immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, supplementation of the diet with omega-3 fatty acids attenuates the production of proinflammatory cytokines (37) and increases the amounts of SPMs in peripheral blood (15, 38). A study identified that omega-3 essential fatty acids, the precursors of SPMs, were biomarkers of a lower risk for fatal coronary heart disease (39, 40). Hence, our results suggest a potential physiologic mechanism by which coagulation initiates the endogenous production of functional n-3-derived SPMs that affect innate immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…a survey questionnaire, 2,5-12,14,15 while 3 studies measured serum or plasma fatty acids using gas-liquid chromatography. 13,16,17 Although fatty acids in blood and adipose tissue have been used as a gold standard to validate dietary polyunsaturated fatty acids, biomarkers of mono-unsaturated and saturated fatty acids are not reflected by fatty acid intake. 18,19 Each individual fatty acid composition in the same classification group or within classification groups can cause different effects with regard to risk of CAD.…”
mentioning
confidence: 99%
“…States but lower concentrations than in Asian countries (i.e., Korea and Japan) (35). Fish-oil supplementation is prevalent in Iceland, which may limit the generalizability of our results.…”
Section: Discussionmentioning
confidence: 58%